2016
DOI: 10.1152/japplphysiol.00284.2016
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of strength and endurance exercise training on COX-2 and mPGES expression in mouse brain are independent of peripheral inflammation

Abstract: Acute endurance exercise has been shown to modulate cyclooxygenase (COX)-2 expression, which is suggested to affect neuronal plasticity and learning. Here, we investigated the effect of regular strength and endurance training on cerebral COX-2 expression, inflammatory markers in the brain, and circulating cytokines. Male C57BL/6N mice were assigned to either a sedentary control group (CG), an endurance training group (EG; treadmill running for 30 min/day, 5 times/wk, 10 wk), or a strength training group (SG; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The increased expression of COX-2 and microsomal prostaglandin E synthase, an enzyme downstream of COX-2, were independent of peripheral inflammation. 138 Exercise improved oxidative stress and inflammation directly at the brain of old high-fat-fed ApoE −/− mice, reaffirming the neuroprotective effects of exercise in a model of mice with vascular brain lesions. 138 On the other hand, aged mice, training above the lactate threshold showed increased levels of brain PGC-1α, mTOR, and phospho-mTOR protein levels, as well as citrate synthase mRNA levels.…”
Section: Immune-regulating Effects Of Exercise Trainingmentioning
confidence: 79%
See 1 more Smart Citation
“…The increased expression of COX-2 and microsomal prostaglandin E synthase, an enzyme downstream of COX-2, were independent of peripheral inflammation. 138 Exercise improved oxidative stress and inflammation directly at the brain of old high-fat-fed ApoE −/− mice, reaffirming the neuroprotective effects of exercise in a model of mice with vascular brain lesions. 138 On the other hand, aged mice, training above the lactate threshold showed increased levels of brain PGC-1α, mTOR, and phospho-mTOR protein levels, as well as citrate synthase mRNA levels.…”
Section: Immune-regulating Effects Of Exercise Trainingmentioning
confidence: 79%
“… 138 Exercise improved oxidative stress and inflammation directly at the brain of old high-fat-fed ApoE −/− mice, reaffirming the neuroprotective effects of exercise in a model of mice with vascular brain lesions. 138 On the other hand, aged mice, training above the lactate threshold showed increased levels of brain PGC-1α, mTOR, and phospho-mTOR protein levels, as well as citrate synthase mRNA levels. 139 A similar relationship has been confirmed in young mice.…”
Section: Immune-regulating Effects Of Exercise Trainingmentioning
confidence: 79%
“…This threshold can be reduced when IL-6 is combined with low doses of other cytokines such as IL-1 (Cartmell et al, 2000 ). Interestingly, low circulating IL-6 levels that also occur during exercise seem to correlate with COX2 expression in the hypothalamus (Kruger et al, 2016 ) but are not accompanied by fever.…”
Section: Discussionmentioning
confidence: 99%
“…Kruger et al recently reported that the COX-2 expression induction is more obvious followingstrength training[42].In summary, concurrent training prevents morphine-induced neurodegeneration via a rise in neurogenesis in the hippocampus DG of rats resulting in synaptic plasticity enhancement.Therefore, exercise training may be an appropriate novel candidate for treating opioid addiction.…”
mentioning
confidence: 84%